Increased levels of MMP-3, MMP-9 and MPO represent predictors of in-stent restenosis, while increased levels of ADMA, LCAT, ApoE and ApoD predict bare metal stent patency - Pleva, Leoš; Kušnierová, Pavlína; Plevová, Pavlína; Zapletalová, Jana; Karpíšek, Michal; Faldynová, Lucie; Kovářová, Petra; Kukla, Pavel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
AIMS: We sought to identify biochemical predictors that indicate susceptibility to in-stent restenosis (ISR) after coronary artery bare-metal stenting. METHODS: A total of 111 consecutive patients with post-percutaneous coronary intervention (PCI) in-stent restenosis of a target lesion within 12 months were matched for age, sex, vessel diameter, and diabetes with 111 controls without post-PCI ISR. Plasma or serum levels of biochemical markers were measured: matrix metalloproteinases (MMP) 2, 3, 9; myeloperoxidase (MPO); asymmetric dimethylarginine (ADMA); lipoprotein (a) (Lp[a]); apolipoproteins E and D (ApoE and D); and lecitin-cholesterol acyltransferase (LCAT). Multivariable logistic regression association tests were performed. RESULTS: Increased plasma MMP-3 (OR: 1.013; 95% CI: 1.004-1.023; P = 0.005), MMP-9 (OR: 1.014; 95% CI: 1.008-1.020; P < 0.0001) or MPO (OR: 1,003; 95% CI: 1.001-1.005; P = 0.002) was significantly associated with increased risk of ISR. Increased levels of ADMA (OR: 0.212; 95% CI: 0.054-0.827; P = 0.026), ApoE (OR: 0.924; 95% CI: 0.899-0.951; P < 0.0001), ApoD (OR: 0.919; 95% CI: 0.880-0.959; P = 0.0001), or LCAT (OR: 0.927; 95% CI: 0.902-0.952; P < 0.0001) was associated with risk reduction. No correlation was found between plasma MMP-2 or Lp (a) and ISR risk. CONCLUSIONS: Increased levels of MMP-3, MMP-9, and MPO represent predictors of ISR after bare-metal stent implantation. In contrast, increased ADMA, LCAT, and Apo E and D indicate a decreased in-stent restenosis occurrence.
Keywords: apolipoproteiny E; Female; biologické markery; Biomarkers; ženské pohlaví; matrixová metaloproteinasa 3; Phosphatidylcholine-Sterol O-Acyltransferase; Arginine; lecitincholesterolacyltransferasa; koronární restenóza; průchodnost cév; lidé; Coronary Restenosis; koronární angioplastika; Apolipoproteins D; studie případů a kontrol; Graft Occlusion, Vascular; Matrix Metalloproteinase 9; Middle Aged; Percutaneous Coronary Intervention; Male; matrixová metaloproteinasa 9; Aged; Apolipoproteins E; Case-Control Studies; Stents; apolipoproteiny D; Vascular Patency; okluze cévního štěpu; Matrix Metalloproteinase 3; arginin; lidé středního věku; senioři; mužské pohlaví; Lipoprotein(a); lipoprotein (a); peroxidasa; stenty; Peroxidase; Humans